2010
DOI: 10.1007/s10143-010-0239-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of stem cell marker CD133 expression with dissemination of glioblastomas

Abstract: Dissemination of glioblastoma was once considered rare but is now increasingly encountered with longer survival of glioblastoma patients. Despite the potential negative impact of dissemination on clinical outcome, however, molecular markers useful for prediction of dissemination risk still remains ill defined. We tested in this study for an association between the expression of stem cell marker CD133 and the risk of dissemination in 26 cases of glioblastoma (16 with dissemination and 10 without dissemination).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…2D and E), which was also suggested in the report by Sato et al 34 According to previous reports, glioma stem cells with high CD133 expression are resistant to chemoradiotherapy 18,35 and grow as floating cells. 36 Thus, these cells may survive the initial treatment and may be able to propagate through CSF, resulting in distant recurrence.…”
Section: Discussionsupporting
confidence: 59%
“…2D and E), which was also suggested in the report by Sato et al 34 According to previous reports, glioma stem cells with high CD133 expression are resistant to chemoradiotherapy 18,35 and grow as floating cells. 36 Thus, these cells may survive the initial treatment and may be able to propagate through CSF, resulting in distant recurrence.…”
Section: Discussionsupporting
confidence: 59%
“…The latter allows targeting of zones with high cell density [23], whereas targeting with perfusion-weighted MRI relates to greater malignant vascularity. Perfusion MRI mapping may be more useful than PET, given that neoangiogenesis is the strongest predictive factor for glial tumors [14,24,25,26]. In the present study, targeting based on perfusion-weighted MRI corresponded to contrast enhancement data for 10 of the 11 glial tumors.…”
Section: Discussionmentioning
confidence: 81%
“…These authors determined that these CD133 + cells were glioblastoma stem cells, and also identified a more aggressive subtype of the disease (21) , insofar as these cells are highly resistant to radiation and chemotherapy procedures (16) . Other studies have also suggested that the expression of the marker CD133 + could be a molecular indicator of glioblastoma spreading (16,22) , which justifies its prognostic value (23) and the recent demand for drugs that act against this subset of cells (CD133 + ) in order to inhibit or retard the proliferation of highly invasive gliomas (24) .…”
Section: Discussionmentioning
confidence: 99%